Administration of a dietary supplement (N-oleyl-phosphatidylethanolamine and epigallocatechin-3-gallate formula) enhances compliance with diet in healthy overweight subjects: a randomized controlled trial - Rondanelli, Mariangela; Opizzi, Annalisa; Solerte, Sebastiano Bruno; Trotti, Rosita; Klersy, Catherine; Cazzola, Roberta (British journal of nutrition, 2009)
Many studies have found that N-oleyl-ethanolamine (NOE), a metabolite of N-oleyl-phosphatidylethanolamine (NOPE), and epigallocatechin-3-gallate (EGCG) inhibit food intake. The main aim of this study was to evaluate the efficacy of 2 months of administration of an oily NOPE–EGCG complex (85 mg NOPE and 50 mg EGCG per capsule) and its effect on compliance with diet in healthy, overweight people. Secondary end-points of the study were to compare body composition, metabolic parameters, sensation of appetite, depressive symptoms and severity of binge eating. Using a parallel-arm, double-blind, placebo-controlled design, 138 healthy, overweight women (106) and men (thirty-two) were randomly assigned to one of two groups: (1) the treatment group (seventy-one patients: fifty-three females, eighteen males) taking two capsules per day of an oral supplement or (2) the placebo group (sixty-seven patients: fifty-three females, fourteen males). Both groups observed a 3344 kJ/d energy restriction. All parameters were assessed both before onset and after 2 months on the supplement. Dropout was 6 % in the NOPE–EGCG group and 27 % in the placebo group (P < 0·001). The treatment induced a significant weight reduction in both groups ( − 3·28 kg and − 2·67 kg in NOPE–EGCG and placebo, respectively); the weight changes were not significantly different between the groups. NOPE–EGCG treatment improved insulin resistance (P < 0·001), the sensation feelings of fullness (P < 0·05), depressive symptoms (P < 0·004) and severity of binge eating (P < 0·0001).